Multilevel methods for Wilson element approximation of elasticity problem - Xu, Xuejun (Computer methods in applied mechanics and engineering, 1999)
In this paper, a multilevel preconditioner and a V-cycle multigrid algorithm are presented for Wilson nonconforming element approximation of elasticity problem. The condition number of the multilevel preconditioner is shown to be bounded by a constant independent of mesh size and mesh level. Moreover, optimal convergence rate of the V-cycle multigrid algorithm is obtained. A numerical example is given to illustrate the efficiency of our methods.